Dietary α‐cyclodextrin reduces atherosclerosis and modifies gut flora in apolipoprotein E‐deficient mice. Issue 8 (24th February 2017) - Sakurai, Toshihiro; Sakurai, Akiko; Chen, Ye; Vaisman, Boris L.; Amar, Marcelo J.; Pryor, Milton; Thacker, Seth G.; Zhang, Xue; Wang, Xujing; Zhang, Yubo; Zhu, Jun; Yang, Zhi‐Hong; et al.
Abstract : α‐Cyclodextrin (α‐CD) has been shown to lower plasma cholesterol in animals and humans; however, its effect on atherosclerosis has not been previously described. Here, apoE‐knockout mice are fed either low‐fat diet (LFD), or Western high fat diet containing either no additions (WD), 1.5% α‐CD (WDA); 1.5% β‐CD; or 1.5% oligofructose‐enriched inulin. Although plasma lipids are similar after 11 weeks on the WD vs. WDA diets, aortic atherosclerotic lesions are 65% less on WDA compared to WD, and similar level with LFD group, which is likely to be associated with changes in the gut flora. Abstract : Scope: α‐Cyclodextrin (α‐CD), a cyclic polymer of glucose, has been shown to lower plasma cholesterol in animals and humans; however, its effect on atherosclerosis has not been previously described. Methods and results: apoE‐knockout mice were fed either low‐fat diet (LFD; 5.2% fat, w/w), or Western high fat diet (21.2% fat) containing either no additions (WD), 1.5% α‐CD (WDA); 1.5% β‐CD (WDB); or 1.5% oligofructose‐enriched inulin (WDI). Although plasma lipids were similar after 11 weeks on the WD vs. WDA diets, aortic atherosclerotic lesions were 65% less in mice on WDA compared to WD ( P < 0.05), and similar to mice fed the LFD. No effect on atherosclerosis was observed for the other WD supplemented diets. By RNA‐seq analysis of 16S rRNA, addition of α‐CD to the WD resulted in significantly decreased cecal bacterial counts in genera Clostridium and Turicibacterium, and significantly increased Dehalobacteriaceae . At family level, Comamonadaceae significantly increased and Peptostreptococcaceae showed a negative trend. Several of these bacterial count changes correlated negatively with % atherosclerotic lesion and were associated with increased cecum weight and decreased plasma cholesterol levels. Conclusion: Addition of α‐CD to the diet of apoE‐knockout mice decreases atherosclerosis and is associated with changes in the gut flora.